Cepharanthine as a Potential Novel Tumor-Regional Therapy in Treating Cutaneous Melanoma: Altering the Expression of Cathepsin B, Tumor Suppressor Genes and Autophagy-Related Proteins - Liu, Yufang; Xie, Yang; Lin, Yao; Xu, Qingfang; Huang, Yunfen; Peng, Mengran; Lai, Wei; Zheng, Yue (Frontiers in Bioengineering and Biotechnology, 2020)
The incidence of primary cutaneous melanoma continues to increase annually and is one of the most aggressive malignancies in humans and need to develop more novel non-surgical therapies. Autophagy and cathepsin B targeted therapy was reported to improve melanoma treatment. Cepharanthine (CEP), a natural alkaloid extracted from the genus Cepharophyllum has been reported to have the function of inhibiting cancers. We found that CEP inhibited human primary cutaneous melanoma cells viability and proliferation in 24 hours in vitro, and topical application or intra-tumoral injection of CEP decreased the growth of cutaneous melanoma in mice within 4 weeks. CEP preparations below 50% concentration did not induce skin irritation and allergy reaction on human skin in vivo. Primary cutaneous melanoma cells incubated with CEP, the expression of cathepsin B was decreased and the LC3-I and LC3-II expression changed in a dose-dependent manner, while p53, p21Cip1p and p16Inka gene expression was up-regulated. We demonstrated the effects of CEP as a novel tumor-regional therapy for cutaneous melanoma and provided a preliminary research basis for future clinical treatment researches and the exploration of integrated treatments with systemic therapy, radiotherapy, and surgery for human primary cutaneous melanoma.